TREATMENT OF MALASSEZIA DERMATITIS IN A DOMESTIC DOG - Satriawan, Erwin; Arjentinia, I Putu Gede Yudhi; Dewi, Ida Ayu Dian Kusuma (Buletin Veteriner Udayana, 2026)
Malassezia dermatitis is a common skin disease in dogs caused by the overgrowth of Malassezia sp., a lipophilic yeast that normally inhabits the skin but may act as an opportunistic pathogen when skin homeostasis is disrupted. This yeast is commonly found in areas with active sebaceous glands and may cause pruritus, alopecia, hyperpigmentation, and chronic skin changes. This report describes a case of a 3-month-old female domestic puppy named Stella, weighing approximately 3 kg, presenting with chronic pruritus accompanied by generalized hair loss that had persisted for approximately one month. Dermatological examination revealed alopecia on the face, ears, neck, and extremities, along with hyperpigmentation, crust formation, and skin thickening consistent with lichenification. Supporting examinations using acetic acid tape preparation (ATP) cytology demonstrated a high number of Malassezia sp., while skin scraping and otic swab examinations did not reveal the presence of ectoparasites or other infectious agents, and trichogram analysis showed a predominance of hairs in the telogen phase, indicating chronic skin stress. The therapy administered consisted of bathing with Sebazole® shampoo as the primary treatment, topical application of apple cider vinegar and virgin coconut oil (VCO) as adjunct therapies to support skin barrier repair, and administration of diphenhydramine as symptomatic therapy to reduce pruritus. After four weeks of treatment, the clinical condition of the case animal showed significant improvement leading to complete recovery, characterized by the resolution of pruritus, skin lesions, and alopecia, along with hair regrowth.